Overwintering survival and regrowth of the invasive plant Eichhornia crassipes are enhanced by experimental warming in winter - W You; D Yu; D Xie; L Yu (Aquatic Biology, 2013)
The distribution of the invasive aquatic plant Eichhornia crassipes is considered to be limited by winter survival. Therefore, winter warming, as well as characteristics of overwintering organs, are expected to affect its distribution and survival. An experiment was conducted to analyze the effects of winter warming and stem base treatments (size or burial) on winter survival, regrowth and thus performance of floating or rooted plants of E. crassipes using a simulated warming system in a greenhouse. Winter warming significantly increased the percentage survival in both forms of the plant and facilitated its regrowth and clonal propagation. Stem base size played an important role in determining survival, regrowth and vegetative propagation. Moreover, water cover and sediment burial of stem bases facilitated overwintering. After winter survival, a larger fraction of the biomass of E. crassipes was allocated to shoots. These results suggest that, with climate warming, the invasive ability of E. crassipes will be enhanced, with distribution spreading to the north into central and north China, favouring plants with large stem bases.